Bar Master: A Gamified Interactive Learning Application for Bartending Qualification Tems - Cañas, Cristy; Flores, April Rose (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study designed, developed, and evaluated Bar Master, an Android-based gamified learning application intended to strengthen bartending students’ knowledge, skills, and competency in tools, equipment, materials, supplies, and bar setup procedures aligned with TESDA standards. The study was anchored in Self-Determination Theory, Flow Theory, and Mobile Learning Frameworks and followed a developmental research design using the Agile System Development Life Cycle. The application was developed through MIT App Inventor and integrated Firebase Realtime Database and TinyDB for online and offline storage. Forty respondents participated, comprising 30 bartending students and 10 instructors from Colegio de Kidapawan and North Valley College Foundation Inc. Fifteen students formed the experimental group and 15 formed the control group. Data were gathered through validated pretest-posttest evaluations and a Unified Evaluation Form assessing usability, functionality, and acceptability. Weighted mean, standard deviation, paired-samples t-test, and independent-samples t-test were applied. Both groups improved, but the experimental group achieved a greater gain, with a very large effect, and significantly outperformed the control group in the posttest. Students rated the application usable, functional, and acceptable, while instructors rated it highly usable, highly functional, and highly acceptable. Challenges concerned interactive features and limited instructional time for familiarizing learners with bartending resources. The study concluded that Bar Master is an effective supplementary tool and recommended instructional integration, content improvement, controlled user access, and distribution through the Google Play Store. The study supports SDG 4 through accessible, technology-enhanced vocational education and contributes to sustainable institutional practice through reusable, self-paced learning and digital performance monitoring.
Keywords: Bartending Education; Bartending Qualification; Gamified Learning Application; Interactive Learning; Mobile Learning; TEMS; TESDA Competencies